2012
DOI: 10.1089/ees.2011.0304
|View full text |Cite
|
Sign up to set email alerts
|

Chlorobenzene Formation from Fly Ash: Effect of Moisture, Chlorine Gas, Cupric Chloride, Urea, Ammonia, and Ammonium Sulfate

Abstract: Polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) are formed jointly with numerous products of incomplete combustion during waste incineration. Chlorobenzenes (CBz) are often cited as surrogates or precursors of PCDD/Fs. Experiments were conducted to investigate the effect of some key parameters on CBz formation, including moisture (H 2 O), chlorine gas (Cl 2 ), cupric chloride (CuCl 2 ), urea [(NH 2 ) 2 CO], ammonia (NH 3 ), and ammonium sulfate [(NH 4 ) 2 SO 4 ]. Cl 2 and CuCl 2 promoted CBz form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Because of general inhomogeneity, the other solid samples were collected by fully mixed multipoint sampling. Pre-treatment of CBzs is depicted in detail by Yan et al (2012). GC-ECD (GC 6890N, Agilent, USA) with a DB-5 column (30 m × 0.25 mm × 0.25 µm) is used to analyze CBzs (DBz to HCBz).…”
Section: Sampling and Analysismentioning
confidence: 99%
“…Because of general inhomogeneity, the other solid samples were collected by fully mixed multipoint sampling. Pre-treatment of CBzs is depicted in detail by Yan et al (2012). GC-ECD (GC 6890N, Agilent, USA) with a DB-5 column (30 m × 0.25 mm × 0.25 µm) is used to analyze CBzs (DBz to HCBz).…”
Section: Sampling and Analysismentioning
confidence: 99%
“…Calibration solutions of the seventeen regulated 2,3,7,8chloro-substituted PCDD/Fs (CSL-CS4), EPA-1613, and twelve PCBs (CS1-CS6), WP-CVS, containing the corresponding 13 C12-labelled compounds in nonane, were obtained from AfriFusion (Pty) Ltd (Midrand) for quantification purposes. The calibration solutions of PCDD/Fs and PCBs covered a concentration range from 0.1 to 400 ng mL -1 and between 0.1 and 200 ng mL -1 , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…A quartz fiber filter and a glass cartridge with polyurethane foam (PUF) were used for collecting particle phase and gas-phase compounds, respectively. A known amount of PCDD/Fs isotopically labeled surrogate standards ( 37 Cl4-2,3,7,8-TeCDD, 13 C-1,2,3,4,7,8-HxCDD, 13 C-2,3,4,7,8-PeCDF, 13 C-1,2,3,4,7,8-HxCDF, and 13 C-1,2,3,4,7,8,9-HpCDF) was spiked into the cartridge before field sampling in order to estimate the collection efficiency of the sampling train. The sampling flow rate was set to 0.225 m -3 min -1 ±10%.…”
Section: Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al [13] also reported that CaO can efficiently inhibit the formation of PCDD/Fs from dioxin precursors. Nitrogen-containing compounds, including NH 3 , urea, and dimethylamine, also effectively inhibit PCDD/F formation [15][16][17][18][19]. Kasai et al [17] reported that the addition of urea did not significantly affect the concentration of NO x in the stack gas.…”
Section: Introductionmentioning
confidence: 99%